Effect of Local Heating on Postprandial Blood Glucose Excursions Using the InsuPad Device: Results of an Outpatient Crossover Study. (November 2014) - Hermanns, Norbert; Bitton, Gabriel; Reimer, André; Krichbaum, Michael; Kulzer, Bernhard; Haak, Thomas
The InsuPad is a medical device to accelerate insulin resorption by applying local heat at the insulin injection site. This crossover study examined the impact of the InsuPad use on postprandial glucose excursions under daily life conditions. In 1 study phase, diabetic patients used the InsuPad when injecting bolus insulin before breakfast and dinner and measured their blood glucose 5 times daily (before breakfast, lunch, and dinner and after breakfast and dinner). In the other study phase, blood glucose measurements were maintained without using the InsuPad. The order of the study phases was randomized. Twenty patients with a high insulin demand took part (30% type 1 diabetes, age 53.7 ± 8.9 years, diabetes duration 14.9 ± 7.4 years; HbA1c 8.3 ± 0.8%; total daily insulin demand 0.97 ± 0.32 IU per kg). Postprandial glucose excursion was reduced by 15.4 mg/dl (95% CI 9.7-21.2 mg/dl; P = .011) after breakfast and dinner if InsuPad was used. The mean blood glucose was lower by 8.8 mg/dl (95% CI 0:3-18:0 mg/dl; P = .099) when using the InsuPad. Safety parameters and the percentage of hypoglycemic (< 60 mg/dl) or hyperglycemic (> 300 mg/dl) blood glucose measurements were not negatively affected by InsuPad use (hypoglycemic values 1.4% vs 1.5%, P = .961; hyperglycemic values 2.6% vs 4.0%, P = .098). Local heating of the insulin injection site by use of the InsuPad device is an effective and safe method to reduce postprandial blood glucose excursions under daily life conditions without negative side effects on the occurrence of low or high blood glucose values.